Brexit and Its Aftermath - Brexit's impact on Asia - Rana, Pradumna Bickram (2016)
The aftermath of Brexit is unfolding, hence its impact on Asia is difficult to assess. It is, however, likely to be moderate and manageable. In response, Asia should strengthen its regional financial safety net.